2021
DOI: 10.1002/advs.202101447
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Cell RNA‐Seq of T Cells in B‐ALL Patients Reveals an Exhausted Subset with Remarkable Heterogeneity

Abstract: Characterization of functional T cell clusters is key to developing strategies for immunotherapy and predicting clinical responses in leukemia. Here, single-cell RNA sequencing is performed with T cells sorted from the peripheral blood of healthy individuals and patients with B cell-acute lymphoblastic leukemia (B-ALL). Unbiased bioinformatics analysis enabled the authors to identify 13 T cell clusters in the patients based on their molecular properties. All 11 major T cell subsets in healthy individuals are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 63 publications
(88 reference statements)
2
25
0
Order By: Relevance
“…These regions can be enriched from single-cell transcriptomes while maintaining cell barcodes to integrate TCR sequencing data with gene expression profiles (18)(19)(20). Recently, TCR sequencing has been applied to solid and blood cancers to tie cell phenotypes to TCR properties, which has allowed for a deeper examination of T-cell subsets via multiple modalities (20)(21)(22). These studies also investigate the phenomenon of T-cell exhaustion, which occurs when cells enter a dysfunctional state in which they lose effector functions, such as proliferation and cytotoxicity, and gain immunoregulatory functions (7,23,24).…”
Section: Introductionmentioning
confidence: 99%
“…These regions can be enriched from single-cell transcriptomes while maintaining cell barcodes to integrate TCR sequencing data with gene expression profiles (18)(19)(20). Recently, TCR sequencing has been applied to solid and blood cancers to tie cell phenotypes to TCR properties, which has allowed for a deeper examination of T-cell subsets via multiple modalities (20)(21)(22). These studies also investigate the phenomenon of T-cell exhaustion, which occurs when cells enter a dysfunctional state in which they lose effector functions, such as proliferation and cytotoxicity, and gain immunoregulatory functions (7,23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AML patients had a trend toward increased mature NK cells (NK CD56 (dim) cells) ( Tang et al, 2020 ). We also found DC-STAMP expression had a correlation with PDCD1 , CD274 , CTLA-4 , and TIGIT which were exhaustion markers of T cells and considered a dysfunction of anti-tumor immunity ( Noviello et al, 2019 ; Wang et al, 2021 ). A recent study showed that PD1-positive/CD8-positive T cells were higher in relapsed AML patients, compared with newly diagnosed AML patients ( Williams et al, 2019 ).…”
Section: Discussionmentioning
confidence: 72%
“…The heterogeneity of immune checkpoint protein expression is related to the effects of immunotherapy, and the heterogeneity of exhausted T cells may be a reason for the lower effects of immunotherapy with PD‐1 inhibitors (Jia et al, 2018; Wang et al, 2021; Williams et al, 2019). In this study, we characterized the profile of TOX expression and co‐expression with PD‐1, Tim‐3, and CD244 in different AML subtypes by using a heatmap to demonstrate the global distribution.…”
Section: Discussionmentioning
confidence: 99%